2009
DOI: 10.1016/j.expneurol.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin expression in adult cat and primate cerebral cortex relates to immature neurons that develop into GABAergic subgroups

Abstract: DCX-immunoreactive (DCX+) cells occur in the piriform cortex in adult mice and rats, but also in the neocortex in adult guinea pigs and rabbits. Here we describe these cells in adult domestic cats and primates. In cats and rhesus monkeys, DCX+ cells existed across the allo- and neocortex, with an overall ventrodorsal high to low gradient at a given frontal plane. Labeled cells formed a cellular band in layers II and upper III, exhibiting dramatic differences in somal size (5–20 μm), shape (unipolar, bipolar, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
128
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 56 publications
14
128
3
Order By: Relevance
“…It is known that canine and feline cells from the external germinal layer continue to divide for as long as 10 weeks postnatally, hence offering favorable conditions for virus replication (17). Moreover, it is widely accepted that the brain is not a completely irreversible postmitotic tissues as previously thought and that even neurogenesis lasts until adulthood of various species in some brain regions (2,11,28). Replication of parvovirus in neurons has already been demonstrated in cats (56) and mice (42), and it is known that certain types of neurons, e.g., cerebellar Purkinje cells, can express the transferrin receptor that is used by canine and feline parvoviruses for viral entry (40,59).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that canine and feline cells from the external germinal layer continue to divide for as long as 10 weeks postnatally, hence offering favorable conditions for virus replication (17). Moreover, it is widely accepted that the brain is not a completely irreversible postmitotic tissues as previously thought and that even neurogenesis lasts until adulthood of various species in some brain regions (2,11,28). Replication of parvovirus in neurons has already been demonstrated in cats (56) and mice (42), and it is known that certain types of neurons, e.g., cerebellar Purkinje cells, can express the transferrin receptor that is used by canine and feline parvoviruses for viral entry (40,59).…”
Section: Discussionmentioning
confidence: 99%
“…In these still-developing young neurons, DCX is present in the cytoplasm, including axons [Francis et al, 1999;Gleeson et al, 1999]. In the brain of adult mammals, DCX is transiently expressed in recently generated cells that migrate and differentiate into neurons [Liu et al, 2008;Xiong et al, 2008;Cai et al, 2009;Luzzati et al, 2009]. In the rat, expression of DCX starts within 1 day after the last division and disappears after 2-3 weeks, when these cells begin to express proteins characteristic for mature neurons, like NeuN [Brown et al, 2003].…”
Section: Reliability Of DCX As a Marker Of Immature Neuronsmentioning
confidence: 99%
“…Since Altman [1962] first reported adult neurogenesis in the neocortex, this claim is still controversial. On the one hand, data have reported the existence of newly generated neurons in the neocortex [Gould et al, 1999;Dayer et al, 2005;Cameron and Dayer, 2008;Cai et al, 2009], and on the other hand results have found no evidence of such neurons [Kornack and Rakic, 2001;Ehninger and Kempermann, 2003;Koketsu et al, 2003]. The presence, targets and extent of tangential migration from the RMS are highly dependent on investigated species, and the functional role of these new neurons is poorly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, Cai et al [2009] did not advocate that these cells migrate from the ventricles into the cortical areas, stating that DCX-positive cells in the piriform cortex are resident. We observed an age-related decrease in DCX and PSA-NCAM expression in the piriform cortex of the bat, as described in the rat [Shapiro et al, 2007], with adult fruit bats displaying weak immunoreactivity in the temporal stream and piriform cortex.…”
Section: Olfactory Systemmentioning
confidence: 99%